SCREENING FOR ANTIMICROBIAL ACTIVITY OF SOME PLANTS USED IN FOLKLORIC MEDICINE IN THE SUDAN (Journal of Veterinary Medicine and Animal Production, 2022)
The present study was carried out to evaluate the antibacterial and antifungal activity of ethanol, water and petroleum ether extracts of four plants used in Sudanese folkloric medicine. The plants tested were Acacia nilotica fruits, Psidum guajava leaves, Lawsonia inermis leaves and Capparis decidua shoot. The plant extracts were tested at four concentrations, 5%, 10%, 15% and 20%, and their antimicrobial activity was assessed using the cup-plate agar diffusion method against five bacteria (Bacillus subtilis, Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa and Klebsiela pneumoniae) and two fungi (Aspergillus niger and Candida albicans). Activity of the plant extracts was compared with that of known antibacterial and antifungal agents. Acasia nilotica extracts showed the highest activity against both bacteria and fungi, followed by those of P. guajava. Ethanolic extract of the four plant species was the most active extract type against all organisms tested, followed by aqueous extract. B. subtilis was the most susceptible bacterium followed by S. aureus and then E. coli. Of the two fungal species, C. albicans was much more susceptible than A. niger, which showed susceptibility only to ethanolic and aqueous extracts of A. nilotica. The activity of extracts is generally increased with their concentrations. Antibacterial activity of the plant extracts was found, in most cases, superior to that of some known antibacterial agents, while their antifungal activity was inferior to that of some antifungal agents.This study showed that ethanolic extract of Acasia nilotica (fruits) is an excellent candidate to be considered for further studies as source of both antibacterial and antifungal agents.